Title 42 and the Impact on Asylum Seekers: Exploring the Effects of its Termination and its Changes on the US Immigration System - Tóth, Szimonetta (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
The repeal of Title 42, an emergency immigration restriction, represents a significant policy shift in how the United States treats migrants who arrive at the southern border, particularly those seeking asylum. For over three years, U.S. border officers used Title 42 to deport hundreds of thousands of migrants to Mexico or their home countries, claiming that their presence could contribute to the spread of the coronavirus. While Title 42 is allegedly a public health policy, it has been utilized to regulate and prevent unauthorized border crossings. Democrats and campaigners have denounced title 42 because it prevents refugees from obtaining asylum, a legal right they normally have once they reach US territory. Republicans described it as an effective border control tool, requesting that Title 42 should be codified into law so that it may be utilized outside of the pandemic setting. The period of Title 42 ended, which created more obstacles than solutions for asylum seekers. As the US ends Title 42, the rules for asylum seeking are changing once again, the United States will revert to Title 8 under the new standards. The Title 8 Code outlines a strict asylum policy which makes it harder for immigrants to file claims and to seek asylum. Under this new regulation everyone coming from Latin-America, except for Mexico, has to face the harsh reality that the requirements of Title 8 make most of them ineligible for asylum. How does the repealing of Title 42 affect the US immigration system and how will it influence the 2024 elections as the termination was introduced at a critical time, when Biden is seeking a second term?